Analysis Of An Organization's Operational Risk Management In The Identification, Evaluation, And Mitigation Of Risks - Wiwiek Neviana Yusuf (International Journal of Business and Quality Research, 2026)
The purpose of this study is to analyze how organizations identify and evaluate operational risks in their daily activities. This study employs a qualitative approach using a literature review (library research) method through the collection of secondary data from scientific journals, books, and relevant documents. Data analysis is conducted using content analysis techniques to conduct reviews and comparisons, as well as to synthesize findings from various previous studies. The research findings indicate that a structured risk identification process can help organizations recognize the multitude of potential risks, whether from internal or external factors. A structured risk evaluation, whether through risk level classification or quantitative approaches such as the Risk Priority Number (RPN), plays a crucial role in determining risk mitigation priorities. Furthermore, planned, integrated, and sustainable risk mitigation has been proven to enhance the effectiveness of risk management and strengthen organizational resilience. However, there remains a gap in the implementation of risk management, particularly in small-scale organizations that tend to adopt informal and reactive approaches. The implications of this research suggest that, theoretically, operational risk management should be understood as an integrated and continuous process across all organizational activities. Practically, organizations are advised to implement a risk management system based on standards—such as ISO 31000—in a structured and documented manner to enhance operational performance and business sustainability